Prevalence of Depression and Generalized Anxiety Disorder in the Epileptic Adults: A Case-Control Study - Lalchand, Santosh Kumar, Shahnaz Shah, Amjad Ali Qureshi, Tazeem Hussain, Amanullah Bhutto, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: The present study aims the determination the frequency of generalized anxiety disorder (GAD) and depression in epileptic individuals and its association with the duration of the disease and frequency of episodes of seizures. Study type: A case-control study Place and Duration: This study was conducted at Ghulam Mohammad Mahar Medical College Sukkur SMBBMU Larkana from February 2021 to February 2022 Methodology: A total of 110 individuals were considered in the study. All of them were young males with a mean age of 23.2±2.5 years. A total of 55 participants were diagnosed with cases of epilepsy and 55 participants were healthy. The healthy individuals were allocated to the control group. Out of the epileptic 55 participants, 15 had temporal lobe epilepsy (TLE) and 40 had extra-temporal lobe epilepsy (ETLE). All the participants had to complete Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI). Results: The frequency of GAD in the epileptic group was 14 (25.45%) and the frequency of depression was 19 (34.55%) which was higher, compared to the control group. The frequency of depression and GAD was more in the TLE group (p<0.276) compared to the ETLE group despite no statistical significance. There was no remarkable correlation between the duration of the disease with depression inventory score and anxiety inventory score. However, a correlation between the frequency of seizures with the BDI and BAI was found in the TLE group. Conclusion: The frequency of depression and GAD seems to be higher in epileptic individuals. An interdisciplinary and multidisciplinary approach is helpful in the treatment of such patients. Keywords: Epilepsy, Generalized Anxiety Disorder, Frequency, Depression, males